Contribution of Vygotskian-Language-Environment to Enhancement of Speaking Skills Among the Students of Fadl Al-Fadhlan - Novitasari, Elina; Inayah, Inayah; Waemamu, Waesama-ae (Tadris Al-'Arabiyyah: Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2025)
The purpose of this study is to describe and qualitatively analyze the implementation of the language environment based on Lev Vygotsky’s theory in the practice of speaking skills among students of Fadl Al-Fadhlan Islamic Institute in Semarang. This research employed a qualitative approach with a descriptive field method, using observation, interviews, and documentation as data collection techniques. Data were analyzed following the Miles and Huberman model, which involves data reduction, data display, and conclusion drawing. The findings reveal that language environment programs—such as compulsory Arabic classes, conversation sessions, lectures, public lectures, and speech training—align with the concepts of social interaction, the Zone of Proximal Development (ZPD), and scaffolding. These programs focus on developing fluency, accuracy, logical structure, communicative competence, vocabulary mastery, clear pronunciation, and students’ confidence in speaking Arabic. However, variations in students’ language proficiency remain a challenge, as the time required to achieve the expected competencies differs. The uniqueness of this study lies in its integration of Vygotsky’s sociocultural theory with applied field analysis in a contemporary Arabic context, providing an original qualitative model that significantly contributes to the development of speaking skill pedagogy in Arabic language education institutions.